Immune Monitoring for Advanced Cell Therapy Trials in Transplantation: Which Assays and When? - Stark, Helen L.; Wang, Hayson C.; Kuburic, Jasmina; Alzhrani, Alaa; Hester, Joanna; Issa, Fadi (Frontiers in Immunology, 2021)
A number of immune regulatory cellular therapies, including regulatory T cells and mesenchymal stromal cells, have emerged as novel alternative therapies for the control of transplant alloresponses. Clinical studies have demonstrated their feasibility and safety, however developing our understanding of the impact of cellular therapeutics in vivo requires advanced immune monitoring strategies. To accurately monitor the immune response, a combination of complementary methods is required to measure the cellular and molecular phenotype as well as the function of cells involved. In this review we focus on the current immune monitoring strategies and discuss which methods may be utilized in the future.